جاں نثار اختر کی تانیثیت "خاموش آواز" کے خطوط کے تناظر میں: Jan Nisar Akhtar's Feminism In the Context of the Letters of "Khamosh Aawaz" (Research Journal Tahqeeqat, 2025)
Jan Nisar Akhtar is a renowned progressive poet of Urdu literature. His progressive thought has also given a new maturity to his feminist vision. A study of his letters, “Khamosh Aawaz”, to his wives, Safia Akhtar (his first wife) and Khadija Akhtar (his second wife), clearly reveals his vision of a new woman. He considers women to be the most beautiful element of Indian culture and does not want to harm their beauty by chaining them to unjust restrictions. He supports the new woman who raises her voice of protest against oppression and abuse and seems ready to rebel. Jan Nisar desires to create a society in which women’s academic, literary, political, and economic talents get a chance to flourish. According to him, the relationship between husband and wife should be based on friendship and equality. Jan Nisar seems to be a supporter of a kind of feminism that is born from the womb of nature and flourishes under the umbrella of civilization and cultural values.